Pengaruh Pengawasan terhadap Peningkatan Kualitas Kinerja pada Dinas Pendidikan Kabupaten Sorong Provinsi Papua Barat Daya - Ali, Muhammad; Kambuaya, Deasy Ludya A; Kambu, Yeheskel; Basnah, Zabur; Irwan, Andi (Jurnal Online Manajemen ELPEI, 2026)
This research aims to analyze the influence of supervision on the performance quality of the Sorong Regenc Education Office, Southwest Papua Province. The research employs a quantitative method involving 58 respondents as the sample. Data collection is carried out using a questionnaire technique. The data analysis utilizes a simple linear regression test. The results of the study show that supervision has a positive but non-significant impact on performance quality. This is evidenced by the obtained significance value. Nevertheless, the role of supervision still contributes to improving the performance quality in the Sorong Regency Education Office, Southwest Papua Province